Curriculum as a Value-Transmission System: Internalizing Religious Moderation through the Curriculum of Pesantren Al-Ikhlash Based on the Salaf Educational Tradition - Muhammad Hambal Shafwan; Mohammad Hasan Bisyri; Muhammad Hanif; Zainal Arifin (Edukasia Islamika : Jurnal Pendidikan Islam, 2026)
Research on religious moderation in Islamic boarding schools (pesantren) has largely conceptualized religious moderation as either an educational outcome or a curricular program, while limited attention has been given to curriculum as an integrated value-transmission system encompassing philosophical, pedagogical, cultural, and leadership dimensions. This study aims to examine how the curriculum of Pesantren Al-Ikhlash, grounded in the salaf educational tradition, internalizes religious moderation through the integration of curriculum philosophy, curriculum structure, the study of kitab kuning (classical Islamic texts), sorogan and bandongan pedagogies, kiai leadership, the hidden curriculum, and institutional culture. The study employed an intrinsic qualitative case study design. Data were collected through in-depth interviews, participant observation, and document analysis and were analyzed using Reflexive Thematic Analysis. The findings reveal that religious moderation is not taught as a stand-alone subject but is systematically embedded throughout the curriculum as an integral education process. The study of kitab kuning provides the epistemological foundation for balanced religious understanding by exposing students to the diversity of classical Islamic scholarship and legitimate scholarly disagreement (ikhtilāf). Meanwhile, sorogan and bandongan function as pedagogical mechanisms for transmitting ethical conduct, intellectual humility, and respect for diversity, while kiai leadership, the hidden curriculum, and institutional culture reinforce value internalization through exemplary leadership and daily pedagogical practices. The study proposes a conceptual model that positions curriculum as an integrated means of transmitting ethical values, thereby extending Islamic curriculum theory by demonstrating that religious moderation constitutes a structural characteristic of the pesantren educational ecosystem rather than merely an instructional outcome. This model contributes to the advancement of value-based curriculum theory in Islamic education and offers a comprehensive framework for developing religious moderation curricula in Islamic educational institutions.